Evidentiary Value of Reconciliation: Developing Professor Elena I. Nosyreva’s Ideas - Natalia S. Zvyagina; Egor S. Trezubov (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Reconciliation of parties involved in a legal case is a significant and actively developing institution of the civil process. The article examines the issues of evidentiary value of information obtained during conciliation procedures in civil law proceedings. Confidentiality is a universal principle of any conciliation procedure used to resolve a conflict arising from civil and public legal relations. Confidentiality requirements predetermine the secrecy of the conciliation procedure itself and the need to keep secret the information obtained during the conciliation. Confidentiality means that the information obtained by the parties and other persons during reconciliation cannot be disclosed. Without an agreement between the parties, relevant information cannot be presented as part of case materials in court or arbitration tribunal, i.e., it has to be recognized as inadmissible evidence. Information is recognized as confidential if it regards lawful actions, concessions, and admissions made by the conciliation parties to achieve reconciliation. An act of reconciliation in civil law proceedings is an appeal that contains the results of reconciliation and is addressed to court or other competent authority, which allows it to act as a legal fact influencing the dynamics of procedural relations. Being an external expression of the dispute resolution procedure, acts of reconciliation are subject to the procedural form of the corresponding dispute resolution procedure. They are addressed to court during the trial and thus cannot be recognized as containing confidential information.